On Karl Marx's 'Ethnological Notebooks'. Issue 3 (2nd October 2021) - Álvares, Lucas Parreira
Abstract : The aim of this article is to understand the specificities of Marx's so-called Ethnological Notebooks, a text that, although invoked in certain discussions, is still unknown by most authors in the Marxist and anthropological traditions. My aim is to advise the reader of the Ethnological Notebooks about the pitfalls and difficulties of its interpretation, to set the historical context in which the texts that compose this volume were written, to review the main readings of such work, to uncover the editorial process that culminated in the traditional edition of Lawrence Krader in 1972, and to criticize the hitherto 'untouchable' interpretation of this editor due to his apparent authority to deal with the properties contained in the thorny Marxian Ethnological Notebooks.